2021
DOI: 10.1140/epjb/s10051-021-00247-z
|View full text |Cite
|
Sign up to set email alerts
|

Energy diffusion of simple networks under the spatiotemporal thermostats

Abstract: We investigate the energy transport in simple networks consisting of one-dimensional nonlinear chain with self-coupled loop. The impacts of the loop length and coupling strength on the heat flux and spatiotemporal correlation functions of energy-momentum fluctuations are discussed via Langevin thermostats generated by spatiotemporal noise. For thermostats at different temperatures, the spatiotemporal ones can weaken the total heat flux of the system in comparison with the normal Langevin ones. The total heat f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Heat conduction has been a research hotspot for many years, with numerous studies investigating its properties and behavior [1][2][3][4][5]. In particular, energy transport in low-dimensional systems has garnered significant attention [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Heat conduction has been a research hotspot for many years, with numerous studies investigating its properties and behavior [1][2][3][4][5]. In particular, energy transport in low-dimensional systems has garnered significant attention [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work also employed networks using a 2D square array of polymer-linked nanoparticles to realize brainlike computing. Another recent work by Li and co-workers showed that heat transfer in a 1D chain network with a self-coupled loop can be affected by the loop length and coupling strength, which may be important in controlled thermal information processing.…”
Section: Introductionmentioning
confidence: 99%